A Closer Look to the Evolution of Neurons in Humans and Apes Using Stem-Cell-Derived Model Systems - Schörnig, Maria; Taverna, Elena (Frontiers in Cell and Developmental Biology, 2021)
The cellular, molecular and functional comparison of neurons from closely related species is crucial in evolutionary neurobiology. The access to living tissue and post-mortem brains of humans and non-human primates is limited and the state of the tissue might not allow recapitulating important species-specific differences. A valid alternative is offered by neurons derived from induced pluripotent stem cells (iPSCs) obtained from humans and non-human apes and primates. We will review herein the contribution of iPSCs-derived neuronal models to the field of evolutionary neurobiology, focusing on species-specific aspects of neuron’s cell biology and timing of maturation. In addition, we will discuss the use of iPSCs for the study of ancient human traits.